PENGARUH KONSEP DIRI TERHADAP RELIGIUSITAS PESERTA DIDIK - Hadikusuma, Surya (UNISAN JURNAL, 2023)
This study aims to prove the effect of self-concept on the religiosity of SMP Datarajan students. The research in this thesis is a quantitative study with a population and sample of 51 self-concepts on the religiosity of SMP Datarajan students. Data collection was carried out through questionnaires and documentation. The validity of the instrument through the Product Moment correlation and the reliability of the instrument through the halving technique. As for data analysis techniques through prerequisite tests with normality tests and homogeneity tests, variable descriptions, and hypothesis testing with simple linear regression tests and multiple regression tests. The hypothesis in this study is that self-concept has a significant direct influence on the religiosity of SMP Datarajan students. Testing the hypothesis using regression analysis and path analysis using SPSS software version 23 with an alpha significance level of 5 percent (α = 0.05). This study resulted in the effect of self-concept on the religiosity of SMP Datarajan students of 0.818 so that the contribution was 18%.